An Analysis of Readiness of Teacher at MAN 2 Tapanuli Tengah In Facing Education Digital Transformation - Kurnia Arifah Pasaribu; Yunita Nadia (Universitas Sebelas Maret, 2026)
The digital transformation in education requires teachers to be well-prepared in adopting technology as an effective teaching medium and method. The study aims to analyze the readiness of teachers at MAN 2 Tapanuli Tengah in facing the digital transformation of education, focusing on three key aspects: technological competence, attitudes and motivation, and supporting facilities and infrastructure. This research employs a quantitative approach with a descriptive method. Data were collected through questionnaires, interviews, and observations involving 35 teacher respondents. The results indicate that the overall readiness of teachers at MAN 2 Tapanuli Tengah is categorized as